Evaluating the mitochondrial activity and inflammatory state of dimethyl sulfoxide differentiated PLB-985 cells. (July 2021) - Jougleux, Jean-Luc; Léger, Jacob L.; Djeungoue-Petga, Marie-Ange; Roy, Patrick; Soucy, Marie-France N.; Veilleux, Vanessa; Hébert, Mathieu P.A.; Hebert-Chatelain, Etienne; Boudreau, Luc H.
Highlights: PLB-985 maturation affects the mitochondrial respiration. 5-lipoxygenase expression is increased following cell differentiation. PLB-985 maturation increases capacity of neutrophil extracellular traps release. Leukotriene B4 is the main 5-lipoxygenase product released from matured PLB-985. Abstract: Neutrophils play a key role in the innate immunity with their ability to generate and release inflammatory mediators that promote the inflammatory response and consequently restore the hemostasis. As active participants in several steps of the normal inflammatory response, neutrophils are also involved in chronic inflammatory diseases such as asthma, atherosclerosis, and arthritis. Given their dual role in the modulation of inflammation, regulating the inflammatory response of neutrophils has been suggested as an important therapeutic approach by numerous researchers. The neutrophils have a relatively short lifespan, which can be problematic for some in vitro experiments. To address this issue, researchers have used the human monomyelocyte cell line PLB-985 as an in vitro model for exploratory experiments addressing neutrophil-related physiological functions. PLB-985 cells can be differentiated into a neutrophil-like phenotype upon exposure to several agonists, including dimethyl sulfoxide (DMSO). Whether this differentiation of PLB-985 affects important features related to the neutrophil's normal functions ( i.e., mitochondrial activity, eicosanoid production) remains elusive, and characterizing these changes will be the focal point of this study. Our results indicate that the differentiation affected the proliferation of PLB-985 cells, without inducing apoptosis. A significant decrease in mitochondrial respiration was observed in differentiated PLB-985 cells. However, the overall mitochondria content was not affected. Immunoblotting with mitochondrial antibodies revealed a strong modulation of the succinate dehydrogenase A, superoxide dismutase 2, ubiquinol-cytochrome c reductase core protein 2 and ATP synthase subunit α in differentiated PLB-985 cells. Finally, eicosanoids (leukotriene B4, 12-hydroxyheptadecatrienoic and 15-hydroxyeicosatetraenoic acids) production was significantly increased in differentiated cells. In summary, our data demonstrate that the differentiation process of PLB-985 cells does not impact their viability despite a reduced respiratory state of the cells. This process is also accompanied by modulation of the inflammatory state of the cell. Of importance, our data suggest that PLB-985 cells could be suitable in vitro candidates to study mitochondrial-related dysfunctions in inflammatory diseases.